1927 Cal. Stat. 938 - (:unkn) unknown (My University, 1927)
ch. 552, §§ 1-2: Prohibited a person, firm, or corporation possessing a machine gun. Punishable by imprisonment up to 3 years and/or fine up to $5,000.
Keywords: MACHINE GUN RESTRICTION